Hepatocyte apoptosis is triggered by hepatic inflammation in common carp acutely exposed to microcystin-LR or chronically exposed to Microcystis - Haoyang Zhao; Kehui Sun; Xiaodan Nan; Weikai Ding; Junguo Ma; Xiaoyu Li (Ecotoxicology and Environmental Safety)
Cyanobacterial blooms pose a serious threat to the survival of fish because of the hepatotoxicity of microcystins produced by toxic cyanobacteria such as Microcystis. Many studies have investigated the hepatotoxicity of microcystins in common carp, a freshwater fish distributed worldwide, but the hepatotoxicity mechanism has not been fully clarified. The present study aimed to investigate the mechanism underlying the hepatic inflammatory response and hepatocyte apoptosis induced by acute microcystin-LR exposure via intraperitoneal injection (71 μg/kg and 119 μg/kg) or gavage (357.08 μg/kg) and chronic exposure to toxic Microcystis blooms. The results of acute exposure revealed that microcystin-LR caused an increase in serum transaminase activity and increased the levels of inflammatory factors and inflammatory mediators, inducing a significant inflammatory response in the liver of common carp. Moreover, biochemical detection revealed that hepatocyte apoptosis occurred in the fish. Moreover, chronic toxic Microcystis exposure also caused hepatic inflammation and subsequent apoptosis mediated by the tumour necrosis factor-α (TNF-α) pathway and the mitochondrial pathway similar to acute exposure. Therefore, our study suggests that the inflammatory response induced by microcystin-LR exacerbates apoptosis, likely mediated by TNF-α. In summary, both acute microcystin-LR exposure and chronic toxic Microcystis exposure can cause inflammation in the liver of common carp, which subsequently triggers hepatocyte apoptosis mediated by the TNF-α pathway and the mitochondrial pathway. This study helps elucidate the mechanism of liver damage induced by cyanobacterial blooms in natural water.